Critical interaction between E1 and E2 glycoproteins determines binding and fusion properties of hepatitis C virus during cell entry. Issue 3 (28th January 2014) - Douam, Florian; Dao Thi, Viet Loan; Maurin, Guillemette; Fresquet, Judith; Mompelat, Dimitri; Zeisel, Mirjam B.; Baumert, Thomas F.; Cosset, François‐Loïc; Lavillette, Dimitri
<x xml:space="preserve">Abstract</x> Hepatitis C virus (HCV) envelope glycoproteins E1 and E2 are important mediators for productive cell entry. However, knowledge about their structure, intra‐ or intermolecular dialogs, and conformational changes is scarce, limiting the design of therapeutic strategies targeting E1E2. Here we sought to investigate how certain domains of E1 and E2 have coevolved to optimize their interactions to promote efficient HCV entry. For this purpose we generated chimeric E1E2 heterodimers derived from two HCV 1a strains to identify and characterize crosstalk between their domains. We found an E1E2 combination that drastically impaired the infectivity of cell culture‐derived HCV particles, whereas the reciprocal E1E2 combination led to increased infectivity. Using HCV pseudoparticle assays, we confirmed the opposing entry phenotypes of these heterodimers. By mutagenesis analysis, we identified a particular crosstalk between three amino acids of E1 and the domain III of E2. Its modulation leads to either a full restoration of the functionality of the suboptimal heterodimer or a destabilization of the functional heterodimer. Interestingly, we found that this crosstalk modulates E1E2 binding to HCV entry receptors SR‐BI and CD81. In addition, we found for the first time that E1E2 complexes can interact with the first extracellular loop of Claudin‐1, whereas soluble E2 did not. These results highlight the critical role of E1 in the modulation of HCV binding to receptors. Finally, we demonstrated that this crosstalk is involved in membrane fusion. Conclusions: These results reveal a multifunctional and crucial interaction between E1 and E2 for HCV entry into cells. Our study highlights the role of E1 as a modulator of HCV binding to receptors and membrane fusion, underlining its potential as an antiviral target. (Hepatology 2014;59:776–788)